Prinsip Etik Keperawatan Respect to Others Berpengaruh Positif dengan Kinerja Perawat - Oktaviarini, Eva; Yetti, Krisna; Afriani, Tuti; Hariyati, Rr Tutik Sri; Wildani, Andi Amalia (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to identify the relationship between the application of nursing ethical principles and nurse performance. The method used was quantitative with a cross-sectional approach to 129 nurses on duty in the Inpatient Room at RSAL Dr. Mintohardjo. Data analysis was carried out using a linear regression test. The research results show that factors related to performance include rank or class (p=0.037), respect for others (r=0.621), compassion (r=0.594), advocacy (r=0.610), intimacy (r=0.608). The regression test shows that 7 variables have a joint influence with the equation Y: 31.864+1.127*Respect to Others + 1.689*Education + 1.179 Length of Work - 1.919 *class rank + 0.755 Intimacy – 1.975*career level + 1.054 Advocacy. Respect to others partially has a positive effect on nurses' performance in nursing care (t=2.433, p=0.016), while the other variables are confounding variables (p>0.05, t<1.98). Variables namely education, rank/class, length of service, career level, advocacy, respect for others and intimacy influence nurse performance with a determined influence of 39.3%. Conclusions from the 4 sub-variables of ethical implementation where these four variables have a significant relationship independently to nurse performance. Keywords: Nurse Performance, Ethical Principles